Correction to: Use of lignocellulosic corn and rice wastes as substrates for oyster mushroom (Pleurotus ostreatus Jacq.) cultivation - Zárate-Salazar, Jhonatan Rafael; Santos, Mirela Natália; Caballero, Erik Nikol Muñoz; Martins, Olívia Gomes [UNESP]; Herrera, Ángel Alfonso Palomo (Springer Nature, 2022)
In subsection 2.8 (Variables analyzed) in the Material and Methods section of the original article, the terms larger diameter and smaller diameter following Eq. 1 should have read major radius (semi-major axis) and minor radius (semi-minor axis), resp. The original article has been corrected.
Correction to: Use of lignocellulosic corn and rice wastes as substrates for oyster mushroom (Pleurotus ostreatus Jacq.) cultivation (SN Applied Sciences, (2020), 2, 11, (1904), 10.1007/s42452-020-03720-z)